40.7k views
4 votes
Solve this pls!!! I need to turn it into
-3
_____
(x+2)(x-5)​

Solve this pls!!! I need to turn it into -3 _____ (x+2)(x-5)​-example-1

1 Answer

6 votes

Explanation:


(-3)/((x+2)(x-5))\qquad\text{use FOIL:}\ (a+b)(c+d)=ac+ad+bc+bd\\\\=(-3)/((x)(x)+(x)(-5)+(2)(x)+(2)(-5))\\\\=(-3)/(x^2-5x+2x-10)\qquad\text{combine like terms}\\\\=(-3)/(x^2-3x-10)


(64x-8x^2)/(10x-80)=(-8x(x-8))/(10(x-8))\qquad\text{cancel}\ (x-18)\\\\=(-8x)/(10)=-(8x:2)/(10:2)=-(4)/(5)x

User Alejandra
by
6.4k points